Gait Analysis of Amputee Dogs Using a Pressure-Sensitive Walkway - Filho, Túlio G.; Rahal, Sheila C.; Kano, Washington T.; Mesquista, Luciane R.; Mamprim, Maria J.; Silva, Jeana P.; Agostinho, Felipe S. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to perform gait analysis using a pressure-sensitive walkway in dogs submitted to high (total) or low amputation (partial) of one forelimb or hindlimb.Study Design A total of 39 dogs met the inclusion criteria. The reasons for the amputations were motor vehicle accidents in 38 dogs and possible limb malformation in 1 dog. The amputee dogs were divided into four groups: G1 (n = 10)—high forelimb; G2 (n = 10)—low forelimb; G3 (n = 9)—high hindlimb; and G4 (n = 10)—low hindlimb. For kinetic evaluation, the dogs were walked across a pressure-sensitive walkway.Results In dogs with forelimb amputation, the percentage of body weight (%BW) distribution on the contralateral forelimb was 50.7% in cases of high amputation and 55.5% in cases of low amputation, while the %BW distribution on the hindlimbs, mainly in the ipsilateral hindlimb, was 27.9% in cases of high amputation and 27.1% in cases of low amputation. In cases of high amputation of the hindlimb, the %BW distribution was 71.5% on the forelimbs and 29.7% on the contralateral hindlimb, while in cases of low amputation, the distribution was mainly for the contralateral hindlimb and ipsilateral forelimb. No statistical difference was noted between the amputation levels, except for the contralateral limb in cases of low and high amputation of the hindlimbs concerning the overload percentage and %BW distribution.Conclusion The amputation level of one forelimb did not influence the %BW distribution; however, in the hindlimb, this was higher for the contralateral limb in dogs submitted to high amputation.
Keywords: limb; walking; kinetic analysis; trauma; amputation